Schedule of Classes, Spring 2008 - University of Wisconsin-Milwaukee. Department of Enrollment Services (University of Wisconsin-Milwaukee, 2007)
PDF version of the UW-Milwaukee Schedule of Courses for the Spring 2008 term. Includes registration policies and lists of available classes during this term.
Keywords: schedule of courses; Department of Enrollment Services; timetables; curriculum; academics